Natural convection analysis for both protruding and flush-mounted heaters located in triangular enclosure - Koca, A.; Öztop, Hakan Fehmi; Varol, Y. (Professional Engineering Publishing Ltd, 2008)
A numerical was performed analysis on laminar natural convection heat transfer and fluid flow in both protruding heaters (PHs) and flush-mounted heaters (FMHs) located in a triangular enclosure using finite-difference technique. The heaters were isothermal and the tern perature of the inclined wall was lower than that of the heaters while the remaining walls of the triangular enclosure were adiabatic. Results are presented according to the location of the heaters in two cases. In the first case, the PH was located near the vertical wall and the FMH near the right corner. In the second case, the PH was located near the right corner of the enclosure, whereas the FMH was located close to the vertical wall. The governing parameters on natural convection were Rayleigh number (10(4) <= Ra <= 10(6)), dimensionless length of the PH (W-1), dimensionless length of the FMH (W-2), dimensionless height of the PH (Hp), dimensionless distance between the heater and the vertical wall (S-1), dimensionless distance between the PH and the FMH (S-2) and aspect ratio of the triangular enclosure (0.25 <= AR <= 1.0). It was found that better heat transfer occured when the PH was located near the right corner of the triangular enclosure, while the other heater was mounted near the left vertical wall. Heaters behaved as a single heater when they were close to each other.
Keywords: natural convection; protruding heater; flush-mounted heater; triangle